Efeitos da dança nas atividades diárias de crianças com Transtorno do Espectro Autista: ensaio clínico randomizado controlado triplo-cego - Rosário, Lívia Maria Ribeiro (2023)
Introduction: Autism Spectrum Disorder (ASD) is defined as a pervasive neurodevelopmental disorder. The clinical characteristics are present from the first stages of child development and cause functional impairment in different aspects of life. In this aspect, the practice of dance, in multiple styles, represents an integrated, low-cost and active approach to the clinical and social aspects of ASD. However, there is a lack of clinical trials regarding delimited outcomes for daily activities, as well as consistent results for this domain. Objectives: To analyze the effects of dance on functional skills in daily activities of children with ASD. Methods: This is a Triple-blind Randomized Clinical Trial with follow-up follow- up, carried out at the Fundação Varginhense de Assistência aos Excepcionais, in Varginha/MG. Children aged 5 to 10 years with a clinical diagnosis of ASD were included, excluding comorbidities. Sociodemographic and clinical variables were collected to characterize the sample. Subsequently, the children were evaluated using the Childhood Autism Rating Scale and the Pediatric Disability Assessment Inventory - Computerized Adaptive Testing (PEDI-CAT). Then, the sample was randomized into two groups: Experimental Group (EG), submitted to dance therapy and multidisciplinary treatment and the Control Group (CG), followed only by multidisciplinary care. Fourteen dance therapy sessions were held lasting 30 to 50 minutes, twice a week, consisting of choreography that explored the movements used during daily activities. The assessments were carried out by two independent, trained researchers during the pre-intervention, post-intervention and follow-up. Comparison analyzes were carried out using SPSS® software, version 20.0 and using the Shapiro Wilk test. The significance level adopted for this study was p<0.05. Results: 112 participants were assessed for eligibility and 26 took part in the study (EG n=14; CG n=12). A significant difference was observed in the intragroup comparison for EG in the daily activities domain (p=0.00; CI= -4.57 to -2.13), in the PEDI-CAT continuous score, as well as in the pre- intervention and follow-up for the same domain (p= 0.00, CI=-3.87 to -1.27). Regarding the normative score, the EG's performance in functional skills was close to that expected for the age group in the domains: daily activities, social-cognitive and responsibility, in intragroup comparisons. No significant differences were observed for the other PEDI-CAT domains, when compared to the CG. Conclusion: Dance, associated with multidisciplinary therapies, maintained gains in functional skills in intergroup comparisons. However, there was a positive impact on the performance of functional skills of children with autism, especially with regard to daily activities, with regard to intragroup comparisons. Positive effects were also found on social cognitive and responsibility activities. No effects were shown on other aspects of functionality.